2015
DOI: 10.1016/j.chemgeo.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium isotope fractionation during shale weathering in the Shale Hills Critical Zone Observatory: Accumulation of light Mg isotopes in soils by clay mineral transformation

Abstract: Magnesium isotopic ratios have been used as a natural tracer to study weathering processes and biogeochemical pathways in surficial environments, but few have focused on the mechanisms that control Mg isotope fractionation during shale weathering. In this study we focus on understanding Mg isotope fractionation in the Shale Hills catchment in central Pennsylvania. Mg isotope ratios were measured systematically in weathering products, along geochemical pathways of Mg during shale weathering: from bedrock to soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 70 publications
4
37
0
Order By: Relevance
“…Those data can be interpreted to imply natural erosion of Sr in plant litter and CWD. The same interpretation is possible for the data from the Shale Hills Critical Zone Observatory, where a similar deficit in heavy Mg isotopes was found in stream and soil water (Ma et al, 2015). In that study the bio-cycling hypothesis was dismissed on the grounds of missing accumulation of Mg in the organic-rich portions of the soil.…”
Section: Accumulation Of Bio-elements During Forest Growth or Export mentioning
confidence: 74%
“…Those data can be interpreted to imply natural erosion of Sr in plant litter and CWD. The same interpretation is possible for the data from the Shale Hills Critical Zone Observatory, where a similar deficit in heavy Mg isotopes was found in stream and soil water (Ma et al, 2015). In that study the bio-cycling hypothesis was dismissed on the grounds of missing accumulation of Mg in the organic-rich portions of the soil.…”
Section: Accumulation Of Bio-elements During Forest Growth or Export mentioning
confidence: 74%
“…Surface adsorption has been shown to have a variable impact on Mg isotope fractionation. Studies using natural samples (Brewer et al, ; Ma et al, ; Opfergelt et al, , ) and laboratory experiments (Wimpenny et al, ) have found that minerals with high fractions of adsorbed Mg, such as kaolinite, preferentially retain 24 Mg. However, other studies have concluded that adsorbed Mg, on gibbsite, for example, is isotopically heavy (Huang et al, ; Liu et al, ; Pogge von Strandmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus subtilis endospore surfaces preferentially adsorb aqueous 24 Mg, much like some mineral surfaces (Brewer et al, ; Ma et al, ; Opfergelt et al, , ; Wimpenny et al, ). In the biotic dialysis assay, the endospores are separated from the forsterite powder by dialysis tubing and cannot interact with the minerals directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations